2016
DOI: 10.1136/bmjopen-2015-010795
|View full text |Cite
|
Sign up to set email alerts
|

Additional follow-up telephone counselling and initial smoking relapse: a longitudinal, controlled study

Abstract: ObjectivesSmoking cessation services can help smokers to quit; however, many smoking relapse cases occur over time. Initial relapse prevention should play an important role in achieving the goal of long-term smoking cessation. Several studies have focused on the effect of extended telephone support in relapse prevention, but the conclusions remain conflicting.Design and settingFrom October 2008 to August 2013, a longitudinal, controlled study was performed in a large general hospital of Beijing.ParticipantsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…For current smoking, in comparison with the migrant dynamics monitoring survey in China [10] in 2013 (54.40% of adult male and 3.70% of adult female were current smokers) and the GATS [19] in 2012 (the prevalence of current smoking was 52.90% for male and 2.35% for female), the prevalence was lower among Songjiang residents both for the male (48.36%) and the female (0.22%). The lower prevalence of smoking especially the current smoking might attribute to the implementation of new Shanghai Tobacco Control Regulation which was enacted in 2016 [20], and the public health education and intervention on smoking cessation in shanghai as well [11, 13]. According to the new Shanghai Tobacco Control Regulation, all public place in Shanghai is smoke free, and violators both of the smokers and the owner of public place will be punished by the government.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For current smoking, in comparison with the migrant dynamics monitoring survey in China [10] in 2013 (54.40% of adult male and 3.70% of adult female were current smokers) and the GATS [19] in 2012 (the prevalence of current smoking was 52.90% for male and 2.35% for female), the prevalence was lower among Songjiang residents both for the male (48.36%) and the female (0.22%). The lower prevalence of smoking especially the current smoking might attribute to the implementation of new Shanghai Tobacco Control Regulation which was enacted in 2016 [20], and the public health education and intervention on smoking cessation in shanghai as well [11, 13]. According to the new Shanghai Tobacco Control Regulation, all public place in Shanghai is smoke free, and violators both of the smokers and the owner of public place will be punished by the government.…”
Section: Discussionmentioning
confidence: 99%
“…But currently, information of TCD prevalence among smokers in China is still unclear. Previous studies demonstrating the role of hospital smoking cessation service in promoting smoking cessation among smokers, and evidence has indicated that smokers receive smoking cessation service increases successful rate in quitting [13, 14]. Similarly, the physical health status such as pregnancy as well as diagnosis of chronic diseases (CD) also promote some smokers to stop smoking [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Other relapse-prevention strategies should also be developed to sustain the effects of smoking cessation interventions. These include self-help materials, telephone follow-ups over a long period [57], and smoking cessation medications [58].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Cigarette smoke contains toxins and carcinogenic substances that contribute to infection, as well as the development of cancer and various diseases. [ 14 18 19 ] One study suggested that the use of tobacco was associated with anal cytological abnormalities by CD4 levels. [ 20 ] Another study indicated that components of tobacco smoke inflict genotoxic damage in the anal epithelium of smokers.…”
Section: Discussionmentioning
confidence: 99%